Effects of propofol on lipopolysaccharide-induced expression and release of HMGB1 in macrophages - Wang,T. (2015)
This study aimed to determine the effects of different concentrations of propofol (2,6-diisopropylphenol) on lipopolysaccharide (LPS)-induced expression and release of high-mobility group box 1 protein (HMGB1) in mouse macrophages. Mouse macrophage cell line RAW264.7 cells were randomly divided into 5 treatment groups. Expression levels of HMGB1 mRNA were detected using RT-PCR, and cell culture supernatant HMGB1 protein levels were detected using enzyme-linked immunosorbent assay (ELISA). Translocation of HMGB1 from the nucleus to the cytoplasm in macrophages was observed by Western blotting and activity of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) in the nucleus was detected using ELISA. HMGB1 mRNA expression levels increased significantly in the cell culture supernatant and in cells after 24 h of stimulating RAW264.7 cells with LPS (500 ng/mL). However, HMGB1 mRNA expression levels in the P2 and P3 groups, which received 500 ng/mL LPS with 25 or 50 μmol/mL propofol, respectively, were significantly lower than those in the group receiving LPS stimulation (P<0.05). After stimulation by LPS, HMGB1 protein levels were reduced significantly in the nucleus but were increased in the cytoplasm (P<0.05). Simultaneously, the activity of NF-κB was enhanced significantly (P<0.05). After propofol intervention, HMGB1 translocation from the nucleus to the cytoplasm and NF-κB activity were inhibited significantly (each P<0.05). Thus, propofol can inhibit the LPS-induced expression and release of HMGB1 by inhibiting HMGB1 translocation and NF-κB activity in RAW264.7 cells, suggesting propofol may be protective in patients with sepsis.